Net-Zero/Positive Energy Buildings and Districts - Hasan, Ala; Reda, Francesco (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Buildings account for more than one-third of the global final energy consumption and CO2 emissions. The building sector offers a significant potential in the transition towards the decarbonisation of societies. To achieve this goal, different concepts and implementations of Net-Zero/Positive Energy Buildings and Districts (NZPEBD) have emerged in the last years and are still in progress. This book is the collection of the articles published in the Special Issue "Net-Zero/Positive Energy Buildings and Districts" of the Buildings journal. This reprint includes 17 research articles covering different aspects of Net-Zero/Positive Energy Buildings and Districts planning, technologies, economics, building design and retrofitting, citizen engagement, and collection of energy data.